1995
DOI: 10.1007/bf02602403
|View full text |Cite
|
Sign up to set email alerts
|

Safety of pneumococcal revaccination

Abstract: Indications for pneumococcal polysaccharide revaccination include highest-risk patients vaccinated more than six years previously, but there is controversy regarding revaccination of patients with chronic medical conditions and revaccination of the elderly. The object of the study was to investigate whether revaccination with the pneumococcal polysaccharide vaccine would cause significant adverse reactions. 151 patients were revaccinated and completed a questionnaire concerning the 72 hours after the injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 1 publication
1
12
0
1
Order By: Relevance
“…These data are derived from studies with tetanus toxoid, 28,29,[89][90][91][92][93] diphtheria toxoid, 94-100 whole cell pertussis, 101 diphtheria/tetanus/acellular pertussis (DTaP) 38,102 and pneumococcal polysaccharide vaccine. 57,81,[103][104][105][106][107][108][109][110] Inflammatory response follows the formation of immune complexes between the circulating antibodies and the injected antigen. This type of reaction is considered to be a Type III hypersensitivity reaction (Arthus reaction).…”
mentioning
confidence: 99%
“…These data are derived from studies with tetanus toxoid, 28,29,[89][90][91][92][93] diphtheria toxoid, 94-100 whole cell pertussis, 101 diphtheria/tetanus/acellular pertussis (DTaP) 38,102 and pneumococcal polysaccharide vaccine. 57,81,[103][104][105][106][107][108][109][110] Inflammatory response follows the formation of immune complexes between the circulating antibodies and the injected antigen. This type of reaction is considered to be a Type III hypersensitivity reaction (Arthus reaction).…”
mentioning
confidence: 99%
“…In one study in 127 patients revaccinated at least 6 years later, 4-8% reported mild systemic reactions (fever, arthralgia, myalgia) and 40-60% reported local reactions (induration, erythema, pain) 40. These incidences of unwanted effects were not much higher than those reported with first vaccination 3638…”
Section: Revaccinationmentioning
confidence: 95%
“…Über 80% der immunkompetenten Erwachsenen zeigen zwei bis drei Wochen nach der Impfung einen Antikör-peranstieg [18,27,31]. Die Antikör-perantwort nimmt mit zunehmendem Alter ab (Abbildung 3).…”
Section: Schutzimpfung Gegen Pneumokokkenunclassified